Animal and Pasture Responses to Grazing Management of Chemically Suppressed Tall Fescue in Mixed Pastures. Issue 5 (1st September 2016) - Williamson, Jessica A.; Aiken, Glen E.; Flynn, Ernest S.; Barrett, Michael
Abstract : Treatment of toxic endophyte‐infected tall fescue [ Lolium arundinaceum (Schreb.) Darbysh] with metsulfuran‐methyl Methyl 2‐[[[[(4‐methoxyl‐6‐methyl‐1, 3, 5‐triazin‐2‐yl)‐amino]carbonyl]amino]sulfonyl] benzoate, as delivered by Chaparral herbicide (Dow AgroSciences, Indianapolis, IN) can mitigate fescue toxicosis and enhance forage nutritive value by suppressing seedhead emergence. A grazing experiment was conducted with steers (2013) and heifers (2014) to evaluate animal and plant responses to grazing management of mixed cool‐season grass pastures treated with Chaparral. Continuous and rotational stocking treatments were assigned to six, 3.0‐ha pastures in a randomized complete block design with three replications in 2013 and two replications in 2014. Each pasture had six tester animals, and stocking rates were varied using put‐and‐take animals. Pastures were grazed from 16 April to 8 July 2013 and 20 May to 12 Aug. 2014. Pasture carrying capacity was 20% greater for rotational than continuous stocking. Calves on rotationally stocked pastures also had 26% greater average daily gain (ADG) and body weight (BW) gain per hectare than those on the continuous treatment. Pre‐grazed herbage had less neutral detergent fiber (NDF) and acid detergent fiber (ADF) than post‐grazed herbage and herbage from continuously stocked pastures in 2013, but they did not differ in 2014. Crude protein (CP) was lower in post‐graze rotational pasture than in continuous or pre‐graze rotational pasture. Fescue roots in rotationally stocked pastures had greater water soluble carbohydrates (WSC) and N concentrations than continuously stocked pastures following the second year of grazing. Results indicated that rotational stocking of Chaparral treated mixed pastures can improve animal performance and pasture productivity.